2015
DOI: 10.1016/j.bbamcr.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

TRPV6 channel modulates proliferation of insulin secreting INS-1E beta cell line

Abstract: Transient receptor potential channel vanilloid type 6 (TRPV6) is a non-selective cation channel with high permeability for Ca²⁺ ions. So far, the role of TRPV6 in pancreatic beta cells is unknown. In the present study, we characterized the role of TRPV6 in controlling calcium signaling, cell proliferation as well as insulin expression, and secretion in experimental INS-1E beta cell model. TRPV6 protein production was downregulated using siRNA by approx. 70%, as detected by Western blot. Intracellular free Ca²⁺… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 56 publications
6
22
0
Order By: Relevance
“…A promitogenic role of TRPVs in insulin producing cells is also supported by our recent data. We found that suppression of TRPV6 protein production by siRNA technique resulted in reduced cell proliferation and viability in INS-1E cells (61). Likewise previous studies, these effects were detected in the presence of glucose and serum.…”
Section: Trpvs In Controlling β-Cell Growth and Deathsupporting
confidence: 64%
See 1 more Smart Citation
“…A promitogenic role of TRPVs in insulin producing cells is also supported by our recent data. We found that suppression of TRPV6 protein production by siRNA technique resulted in reduced cell proliferation and viability in INS-1E cells (61). Likewise previous studies, these effects were detected in the presence of glucose and serum.…”
Section: Trpvs In Controlling β-Cell Growth and Deathsupporting
confidence: 64%
“…Recently, however, we reported that TRPV6 mRNA is expressed in rat INS-1E cells and rat pancreatic islets (61). Using double immunofluorescence staining we detected that TRPV6 is expressed in rat β-cells.…”
Section: Trpv6mentioning
confidence: 99%
“…The consequences of TRPV6 down-regulation in BON-1 cells on NFAT activity were assessed using NFAT reporter assay (Qiagen) 48 h after TRPV6 siRNA transfection, as previously described in our earlier study [15]. …”
Section: Methodsmentioning
confidence: 99%
“…The consequences of TRPV6 down-regulation in BON-1 cells on cell cycle were determined using propidium iodide (PI) staining 48 h after siRNA transfection, as described [15]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation